Henry Van Dyke postcard and poem - Van Dyke, Henry, 1852-1933.
Postcard (1923 December 6) written by Van Dyke to Cordelia Jackson thanking her for a gift of walnuts; and holograph poem (undated) by him entitled, "The Name of France."
Author, clergyman, diplomat, educator, and poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Jackson, Cordelia -- Correspondence; American poetry -- 20th century; Walnut; France -- Poetry; Authors; Clergy; Diplomats; Educators; Poets